Mitigasi Risiko dalam Aktivitas Perdagangan Buah di Kota Makassar - Azrarul Amri; Rismaladewi Maskar Maskar; Arini Mayang Fauni Fauni (Ma'soem University, 2026)
Fruit trading in traditional markets faces various business risks arising from the perishable nature of horticultural products, supply fluctuations, changing consumer demand, and increasing market competition. These conditions may affect business sustainability if risks are not properly identified and managed. This study aimed to identify business risks, evaluate risk levels based on likelihood and impact, and formulate appropriate risk mitigation strategies for fruit traders in Makassar City, Indonesia. A quantitative descriptive approach was employed. Data were collected through observations, interviews, and questionnaires administered to 100 fruit traders selected using Cochran’s formula and simple random sampling. Risk analysis was conducted using a risk assessment matrix based on likelihood and impact criteria in accordance with the ISO 31000 risk management framework. The results identified twelve business risks distributed across three operational stages: preparation, sales, and closing activities. Risk evaluation indicated that one risk, namely competition among fruit traders (R8), was classified as a crisis risk; seven risks were categorized as high risk, primarily related to supply, product quality, and market dynamics; three risks were classified as medium risk; and one risk was categorized as low risk. The proposed risk treatment strategies include strengthening supplier partnerships, improving product quality and postharvest handling, enhancing operational management, adopting digital marketing, and improving market cleanliness and security. The study concludes that systematic risk management enables fruit traders to prioritize risk treatment and enhance business resilience and sustainability.